Preparo e caracterização de compósitos polímero/cerâmica com potencial aplicação como sensor multifuncional - Macario, Leilane Roberta [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research aimed the preparation and study of polymer/ceramic composites with potential applications as multifunctional sensors, to be used for converting mechanical into electrical energy as well as for light emissions. Different perovskite ceramics powders (pure and doped with europium) were obtained by the Polymeric Precursor Method in order to establish the optimization of piezoelectric and luminescent properties. The composite films were formed by the junction of ceramic powders with poly vinylidene fluoride polymer. The results obtained in this study were divided into three topics. In the first topic ceramic materials BaZrxTi1-xO3 (x = 0, 0.05, 0.08, 0.1, 0.25, 0.50, 0.75 and 1) were obtained and characterized. In the second topic were collated and analyzed the ceramic samples doped with ions Eu3+: Ba1-yEuyZr0,08Ti0,92O3, Ba1-yEuyTiO3, and Ba1- yEuyZrO3 with (y = 0.005, 0.01, 0.02, and 0.04). In the third topic several variables were tested in order to optimize the composites formation using the best conditions. The composites that were obtained in the optimized conditions were analyzed. For structural characterization were used the X-Ray Diffraction and Raman Spectroscopy techniques. The optical property was analyzed by Reflectance Spectroscopy in the UV-Vis range and Photoluminescence measurements. The ceramic surface morphology and the ceramic distribution in the polymer were studied by Scanning Electron Microscopy Field Emission Gun. The electrical conductivity, the longitudinal piezoelectric coefficient d33, and hysteresis curves of these materials were the tools used to analyze their electrical properties. All composites showed the piezoelectricity and the photoluminescence properties and therefore are able to be applied as a multifunctional sensor.

Este trabalho teve como meta o preparo e o estudo de compósitos polímero/cerâmica com potencial para aplicação como sensor multifuncional, para ser utilizado, tanto para conversão de energia mecânica em energia elétrica bem como para emissão de luz. Para a preparação desse compósito, diferentes pós cerâmicos de estrutura perovskita puros e dopados, com a terra-rara európio (Eu), foram obtidos via Método dos Precursores Poliméricos. Estes pós foram preparados com o objetivo de estabelecer a otimização das propriedades piezoelétricas e luminescentes. Por outro lado os pós misturados ao polímero poli fluoreto de vinilideno (PVDF), formaram os filmes compósitos. Os resultados obtidos neste trabalho foram divididos em 3 tópicos. No primeiro tópico os materiais cerâmicos de BaZrxTi1-xO3 com (x = 0; 0,05; 0,08; 0,1; 0,25; 0,50; 0,75 e 1) foram obtidos e caracterizados. No segundo tópico foram sintetizadas e analisadas as amostras cerâmicas dopadas com íons Eu; Ba1-yEuyZr0,08Ti0,92O3, Ba1-yEuyTiO3 e Ba1-yEuyZrO3 com (y = 0,005; 0,01; 0,02 e 0,04). No terceiro tópico as cerâmicas de melhores propriedades piezoelétricas formaram compósitos com o polímero PVDF em condições que foram otimizadas. Para a caracterização estrutural foram utilizadas as técnicas de Difratometria de Raios-X e a Espectroscopia Raman. A propriedade ótica foi analisada por Espectroscopia de Reflectância no Ultravioleta e Visível e Fotoluminescência. A morfologia das cerâmicas e a superfície e a distribuição da cerâmica no polímero foram observadas por Microscopia Eletrônica de Varredura de Emissão de Campo. A condutividade elétrica, o coeficiente piezelétrico longitudinal d33 e as curvas de histerese foram as ferramentas utilizadas para análise das propriedades elétricas. Todos os compósitos formados apresentaram as propriedades de piezoeletricidade e de fotoluminescência, portanto, possuem condições para serem aplicados como...
Keywords: Físico-química; Resinas compostas; Piezoeletricidade; Fotoluminescencia; Piezoelectricity